2019
DOI: 10.4274/tjps.59320
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, antifungal and antioxidant activity of Cleome coluteoides: An In Vitro Comparative Study between Leaves, Stems, and Flowers

Abstract: Objective: Cleome coluteoides belongs to Capparidaceae family and has been used in folk medicine for a long time. The aim of our research was measuring the antioxidant, antibacterial and antifungal activities of C. coluteoides. Materials and Methods: different parts of plant were extracted by various solvents (ethyl acetate, methanol and dichloromethane). Antibacterial and antifungal activities were assayed by disk and well diffusion methods. The antioxidant activity was screened by DPPH and FRAP methods. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The methanol extract of the leaf and the ethyl acetate extract of flowers had the highest antioxidant and antimicrobial activities, respectively, which are probably related to the total phenolics content. 37…”
Section: Discussionmentioning
confidence: 99%
“…The methanol extract of the leaf and the ethyl acetate extract of flowers had the highest antioxidant and antimicrobial activities, respectively, which are probably related to the total phenolics content. 37…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study reported by Deventhiran et al (2017) and Jana and Biswas (2011) showed that C. viscosa is used to treat infection, and lactam nonanoic acid is isolated from its root exudates has inhibitory activity on fungi due to its allelopathic and antimicrobial properties. Besides, Moghaddam et al (2021) reported that C. coluteoides has antifungal activity against Fusarium solani and Candida albicans while Gowdra et al (2019) stated that C. isocandra is able to inhibit the mycelial growth and spore germination of Alternaria solani Sorauer.…”
Section: Introductionmentioning
confidence: 99%